Allan Quatermain - Haggard, H. Rider (Henry Rider), 1856-1925 (Open Road Integrated Media, 2016)
The heroes of King Solomon's Mines return to Africa in this action-packed sequel that inspired the film Allan Quatermain and the Lost City of Gold. Allan Quatermain, big-game hunter and explorer, has recently lost his son, Harry, to smallpox and is ready to get away from civilization. Rather than continue to wallow in grief surrounded by his trophies and guns in England, he instead chooses adventure and journeys to eastern Africa with his friends, Sir Henry Curtis and Capt. John Good. With Zulu chief Umslopogaas accompanying them, they head to uncharted territory in search of the Zu-Vendis, a race of white-skinned people rumored to be isolated from the other tribes of Africa and ruled by two beautiful sister queens. There, the travelers confront angry Zu-Vendi priests who admonish the men for killing their sacred hippopotamuses-and Curtis unwittingly becomes part of a tumultuous love triangle with the sister queens. Soon, the party of adventurers finds themselves embroiled in a civil war. Each queen is now vying for the throne, but only one faction will win-and not everyone will survive.